DIGITAL IMAGE PROCESSING BY USING PASS BAND MODULATION TECHNIQUES - Sandip R.Udawant; Satyawati S.Magar (International Journal of Innovations in Engineering Research and Technology, 2021)
Now a days there is use of telecommunication is day today life. Use of Carrier Wave modulation techniques for the image processing is the challenge in the field of communication. This paper introduces the Digital image processing using shift keing techniques. The selection of modulation scheme depends on Bit Error Rate (BER), Peak Signal to Noise Ratio (PSNR), Available Bandwidth. The basic criteria for best modulation technique are Power efficiency, better Quality of Service, cost effectiveness, bandwidth efficiency and system complexity.